2014
DOI: 10.3390/ijms151121587
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Antagonists and Anti-Prostate Cancer Activities of Some Newly Synthesized Substituted Fused Pyrazolo-, Triazolo- and Thiazolo-Pyrimidine Derivatives

Abstract: A series of substituted pyrazole, triazole and thiazole derivatives (2–13) were synthesized from 1-(naphtho[1,2-d]thiazol-2-yl)hydrazine as starting material and evaluated as androgen receptor antagonists and anti-prostate cancer agents. The newly synthesized compounds showed potent androgen receptor antagonists and anti-prostate cancer activities with low toxicity (lethal dose 50 (LD50)) comparable to Bicalutamide as reference drug. The structures of newly synthesized compounds were confirmed by IR, 1H-NMR, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The reaction of compound 1 with ethoxymethylene malomonitrile afforded the corresponding 3-amino-4-cyanopyrazolo derivatives 2, which was treated with formamide or hydrazine hydrate to produce the corresponding 3-aminopyrazolopyrimidine 3 and aminopyrazolopyrazole derivative 4, respectively [18] (Scheme 2). 19) corresponding to the molecular formula C 16 H 10 N 6 S and at 120 (100, base peak).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction of compound 1 with ethoxymethylene malomonitrile afforded the corresponding 3-amino-4-cyanopyrazolo derivatives 2, which was treated with formamide or hydrazine hydrate to produce the corresponding 3-aminopyrazolopyrimidine 3 and aminopyrazolopyrazole derivative 4, respectively [18] (Scheme 2). 19) corresponding to the molecular formula C 16 H 10 N 6 S and at 120 (100, base peak).…”
Section: Methodsmentioning
confidence: 99%
“…In previous work we have reported that certain of substituted pyrazole and oxazole heterocycles represent class of compounds that play an important role in the medicinal chemistry. Previously we have reported the SARS-CoV 3C-like protease inhibitors [10], against different cancer cell lines [11][12][13], EGFR and VEGFR-2 kinase inhibitors [14] activities for different series of substituted pyrazole derivatives. On the other hand, the oxazole heterocyclic derivatives have effective pharmacological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Ar-H) 13. C NMR spectrum, δ, ppm: 13.81, 21.79, 25.87, 26.45, 29.54, 36.55, 38.47, 43.96, 47.50, 48.28, 50.68, 58.19, 112.80, 115.32, 124.22, 125.88, 126.40, 126.50, 132.36, 135.90, 138.54, 147.17, 149.62, 153.62, 164.81, 218.50 (30 C).…”
mentioning
confidence: 99%
“…The heterocyclic pyrazole compounds has been used as; antipyretic, analgesic and anti-inflammatory drug (Sukuroglu et al, 2005), antimalarial (Cunico et al, 2006), antitumor (Naito et al, 2002), antibacterial, antifungal (Akbas et al, 2005), antiparasitic (Rathelot et al, 2002) and antiviral uses (Ding et al, 1994). In addition, pyrimidine derivatives have significant biological activity and anti-prostate cancer (Bahashwan et al, 2014), anti-inflammatory (Ouf et al, 2008), bactericidal (Hossan et al, 2012) and anxiolytic activities (Wagner et al, 2004). Recently, design, synthesis and pharmacological properties of heteroaryl pyrimidine derivatives (Khan et al, 2015) and used as CB 2 cannabinoid receptor partial agonists (Tabrizi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%